2015
DOI: 10.1093/jxb/erv149
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 14-3-3 protein GRF9 in root growth and response under polyethylene glycol-induced water stress

Abstract: Plant 14-3-3 proteins are phosphoserine-binding proteins that regulate a wide array of targets via direct protein-protein interactions. In this study, the role of a 14-3-3 protein, GRF9, in plant response to water stress was investigated. Arabidopsis wild-type, GRF9-deficient mutant (grf9), and GRF9-overexpressing (OE) plants were treated with polyethylene glycol (PEG) to induce mild water stress. OE plant showed better whole-plant growth and root growth than the wild type under normal or water stress conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 36 publications
2
50
0
2
Order By: Relevance
“…Interestingly, AtGRF9, a Ca 2+ -regulated 14-3-3 protein, although not predicted to be located in chloroplasts, has been demonstrated to be present in many compartments, including plastids. This regulatory protein is involved in root and leaf development under water stress (He et al, 2015) and leaf development in general (Omidbakhshfard et al, 2018), but its role in chloroplasts has not yet been explored. The presence of members of protein families involved in Ca 2+ transport/sensing supports the idea of a core-machinery determining the observed Ca 2+ transients in the chloroplast stroma, and putatively in the thylakoid lumen as well.…”
Section: Current Knowledge Of the Molecular Players Involved In Ca 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, AtGRF9, a Ca 2+ -regulated 14-3-3 protein, although not predicted to be located in chloroplasts, has been demonstrated to be present in many compartments, including plastids. This regulatory protein is involved in root and leaf development under water stress (He et al, 2015) and leaf development in general (Omidbakhshfard et al, 2018), but its role in chloroplasts has not yet been explored. The presence of members of protein families involved in Ca 2+ transport/sensing supports the idea of a core-machinery determining the observed Ca 2+ transients in the chloroplast stroma, and putatively in the thylakoid lumen as well.…”
Section: Current Knowledge Of the Molecular Players Involved In Ca 2+mentioning
confidence: 99%
“…The N-terminal domain (NTD) of AtcMCU harbours motifs rich in acidic residues, one of which (107-118) playing a role in Ca 2+ uptake by cMCU, as demonstrated by mutagenesis studies (D107A/E118K mutant) and Ca 2+ uptake assays in an aequorinbased E. coli system (Teardo et al, 2019). Two groups independently set up the same system to study MCU activity, Mayfield et al, 2012;He et al, 2015;Liu et al, 2017;Omidbakhshfard et al, 2018 At4g08810 AtSUB1 Calcium binding protein plastid, nucleus, ER, Golgi, Golgi cryptochrome and phytochrome coaction Guo et al, 2001;Parsons et al, 2012 At4g34070 namely that exploiting E. coli stably expressing aequorin (Teardo et al, 2019) or the fluorescent Ca 2+ reporter GCaMP2 (Fan et al, 2018). This valuable tool allows a quick screening of the effect of MCU residues' mutations and of chemical modulators on the Ca 2+ flux-mediating activity and may become a method of choice for further structure-function studies.…”
Section: Structural and Functional Comparison Between Mcu Isoforms Frmentioning
confidence: 99%
“…Cotton ( Gossypium hirsutum ) and Arabidopsis thaliana plants overexpressing the 14-3-3 gene AtGF14λ (Yan et al, 2004) and A. thaliana plants overexpressing the 14-3-3 gene AtGRF9 (He et al, 2015) each showed improved drought tolerance. On the other hand, a 14-3-3λ and 14-3-3κ double mutant showed enhanced salt resistance (Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A localização das 14-3-3 em diversos compartimentos sub-celulares demonstra seu potencial regulatório em toda a célula (DE LILLE et al, 2001; e sua função biológica é principalmente interagir com proteínas cliente específicas e causar um efeito que altera a cliente, que estão envolvidas em diversas funções. As 14-3-3 estão envolvidas com diversos processos regulatórios como resposta a estresse, transdução de sinais, controle do ciclo celular e apoptose (FERL et al, 2002;FORD et al, 1994;HE et al, 2015;VAN HEMERT et al, 2001).…”
Section: Estrutura E Funções Das Proteínas 14-3-3unclassified
“…Arabidopsis thaliana cujas funções conhecidas são alocação de carbono para crescimento da raiz sob estresse hídrico leve(HE et al, 2015), desenvolvimento dos cloroplastos (MAYFIELD; PAUL; FERL, 2012), sinalização para o florescimento via sistema fotossensível, ao interagir com CONSTANS, um regulador central da via de fotoperíodo(MAYFIELD et al, 2007) e respostas em adaptação ao estresse por calor intenso(DOBRÁ et al, 2015). A proteína GRF9 (F4IP55_ARATH) possui 276 aminoácidos e 30,96 kDa.…”
unclassified